Profil Pengetahuan dan Keyakinan Vaksinasi Covid-19 Aztrazeneca dan Sinovac sebagai Upaya Pencegahan Covid-19 pada Warga Surabaya: Profile of AztraZeneca and Sinovac Covid-19 Vaccination Knowledge and Belief as an Effort to Prevent Covid-19 in Surabaya - Ira Purbosari; Muhammad Wahyono (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Coronavirus disease infection 2019 (Covid-19) has infected tens of millions of people in a worldwide pandemic. The main cause of COVID-19 is SARS-CoV-2. Prevention of transmission is carried out by vaccination against COVID-19. The absorption capacity of COVID-19 is still low, so an analysis of the knowledge and confidence profile of COVID-19 vaccination in the community is carried out. The main thing from this research is to look at the relationship between knowledge of people's attitudes towards Covid-19 vaccination. The method used for data sampling is analytic observational research with cross sectional method, with 380 Surabaya residents as respondents who were selected by consecutive sampling technique through questionnaire data collection. The population of this study were all residents of Surabaya who had completed the phase I and phase II vaccinations. In this study, using a data collection sheet to record secondary data on AEFI incident sheets from the Surabaya City Health Office and using a survey method through questionnaires distributed to subjects. Data analysis used statistical analysis of logistic test. From the results of the study, as many as 77.8% of the public knew about the COVID-19 vaccine, categorized with a very good score. This high score indicates a high level of public trust. So this is proven by the increasing level of confidence by 83.1%, it is proven that respondents have a positive attitude towards the success of controlling COVID-19. This study shows that there is a 94.7% relationship between knowledge of public attitudes towards Covid-19 vaccination, therefore knowledge and belief need to be carried out to the community so that the intention to carry out COVID-19 vaccination increases, so that it will suppress the rate of virus transmission.